Effects of an implicit-explicit hybrid learning model on handball tactical knowledge - Lucas C. Ribeiro; Gibson M. Praça; Lucas S. Figueiredo; Sarah G. T. Bredt; Juliana O. Torres; Pablo J. Greco (Termedia Publishing House, 2022)
Purpose This study aimed to analyse the effect of an implicit-explicit hybrid learning model on declarative and procedural tactical knowledge of young school handball players. Methods Overall, 30 female handball players (mean age: 13.03 ± 0.75 years) from 2 school teams participated in 25 handball training sessions involving activities focused on both implicit and explicit learning. Declarative knowledge was assessed by using the players' analyses of 15 handball video scenes, while procedural knowledge was assessed by analysing the players' actions during a 3 vs. 3 ball possession game. Results The results showed a significant increase in declarative knowledge ( t (23) = -4.228; p < 0.001; d = 0.863) but not in procedural knowledge ( p > 0.05). Conclusions We concluded that the Iniciação Esportiva Universal model improved the declarative knowledge of school handball athletes.